2006
DOI: 10.1007/s00239-005-0201-5
|View full text |Cite
|
Sign up to set email alerts
|

Sauria SINEs: Novel Short Interspersed Retroposable Elements That Are Widespread in Reptile Genomes

Abstract: SINEs are short interspersed retrotransposable elements that invade new genomic sites. Their retrotransposition depends on reverse transcriptase and endonuclease activities encoded by partner LINEs (long interspersed elements). Recent genomic research has demonstrated that retroposons account for at least 40% of the human genome. Hitherto, more than 30 families of SINEs have been characterized in mammalian genomes, comprising approximately 4600 extant species; the distribution and extent of SINEs in reptilian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 80 publications
3
57
0
Order By: Relevance
“…PLEs are a widespread, yet poorly studied, class of transposable elements characterized by an endonuclease domain as well as an unusual but active reverse transcriptase domain with similarity to telomerases (Evgen'ev and Arkhipova 2005). Sauria SINEs are nonviral tRNA-derived repetitive sequences that are widespread in lizards and snakes (Piskurek et al 2006). These elements contain RNA polymerase III-specific internal promoter sequences whose activity can be enhanced by upstream genomic sequences.…”
Section: Discussion Accumulation Of Retrotransposons In Lizard Hox Gementioning
confidence: 99%
“…PLEs are a widespread, yet poorly studied, class of transposable elements characterized by an endonuclease domain as well as an unusual but active reverse transcriptase domain with similarity to telomerases (Evgen'ev and Arkhipova 2005). Sauria SINEs are nonviral tRNA-derived repetitive sequences that are widespread in lizards and snakes (Piskurek et al 2006). These elements contain RNA polymerase III-specific internal promoter sequences whose activity can be enhanced by upstream genomic sequences.…”
Section: Discussion Accumulation Of Retrotransposons In Lizard Hox Gementioning
confidence: 99%
“…Our initial sequence analyses revealed that sequences of Sauria SINE subfamilies described for varanid lizards [Varanus indicus (mangrove monitor)] and snakes [Azemiops feae (Fea's viper)] are closely related to the TATV-SINE (12). These squamates belong to a clade recently defined as Toxicofera, referring to the presence of venom in this phylogenetic lineage (32,33).…”
Section: Resultsmentioning
confidence: 99%
“…Sauria SINEs are Ϸ350 nucleotides long and are widely distributed among lizards and snakes, the most diverse group of living reptiles (Squamata). They comprise a typical 5Ј tRNA-related region, a tRNA-unrelated region, and a 3Ј tail region (containing short tandem repeats) which is derived from ubiquitous squamate Bov-B LINEs (12). Using the complete TATV genome sequence (accession no.…”
Section: Resultsmentioning
confidence: 99%
“…In sauropsids, the most intensively investigated TEs have been non-LTR retrotransposons (LINEs or retroposons), such as RTE clade (including Bov-B LINEs) [Zupunski et al, 2001;Gogolevsky et al, 2008;Novick et al, 2009;Piskurek et al, 2009], L2 clade [Lovsin et al, 2001;Novick et al, 2009;Piskurek et al, 2009], L1 clade [Kordis et al, 2006;Novick et al, 2009;Piskurek et al, 2009], R4 clade [Volff et al, 2001a;Novick et al, 2009;Piskurek et al, 2009], CR1 clade [Fantaccione et al, 2004;International Chicken Genome Sequencing Consortium, 2004;Wicker et al, 2005;Shedlock, 2006;Kaiser et al, 2007;Kriegs et al, 2007;Shedlock et al, 2007;Abrusan et al, 2008;Chapus and Edwards, 2009;Liu et al, 2009;Novick et al, 2009;Piskurek et al, 2009;Shan et al, 2009] and R2 clade [Kojima and Fujiwara, 2005]. Much research in sauropsids has been focused on SINEs, such as on the CR1 LINE/SINE pair in a lizard [Fantaccione et al, 2004], LF SINEs [Bejerano et al, 2006], AmnSINE1s [Nishihara et al, 2006;Hirakawa et al, 2009], Sauria SINEs [Piskurek et al, 2006[Piskurek et al, , 2009Piskurek and Okada, 2007;Gogolevsky et al, 2008;Kosushkin et al, 2008], polIII/SINE in turtles …”
Section: Investigations In the Genomics Era (From The Year 2000 To Thmentioning
confidence: 99%